2018
DOI: 10.1021/acs.jpcc.7b12469
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous Orientational and Conformational Molecular Dynamics in Solid 1,1,2-Trichloroethane

Abstract: The molecular dynamics in the ambient-pressure solid phase of (1,1,2)trichloroethane is studied by means of broadband dielectric spectroscopy and molecular dynamics simulations. The dielectric spectra of polycrystalline samples obtained by crystallization from the liquid phase exhibit, besides a space-charge relaxation associated with accumulation of charges at crystalline domain boundaries, two loss features arising from dipolar 2 molecular relaxations. The most prominent and slower of the two loss features i… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2018
2018
2019
2019

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 56 publications
1
5
0
Order By: Relevance
“…We demonstrate that the out-of-plane rotations are accompanied by a small change of the molecular plane, in particular, by a change of the orientation of the C–Cl bond. The in-plane rotations proposed early by Fujimori and Oguni can only appear as short-lived molecular fluctuations undetectable by X-ray diffraction; they must therefore involve at least one nonequilibrium configuration as it was recently found in some haloethane compounds. , These results allow a microscopic identification of both the primary and secondary dielectric relaxation processes that we observe experimentally.…”
Section: Introductionsupporting
confidence: 76%
“…We demonstrate that the out-of-plane rotations are accompanied by a small change of the molecular plane, in particular, by a change of the orientation of the C–Cl bond. The in-plane rotations proposed early by Fujimori and Oguni can only appear as short-lived molecular fluctuations undetectable by X-ray diffraction; they must therefore involve at least one nonequilibrium configuration as it was recently found in some haloethane compounds. , These results allow a microscopic identification of both the primary and secondary dielectric relaxation processes that we observe experimentally.…”
Section: Introductionsupporting
confidence: 76%
“…Disorder in the solid-state structures of various chlorocarbons (1,1,2-trichloroethane, , 1,1,2,2-tetrachloroethane, 1,2-dichloroethane) has been a topic of interest. The positioning of the relatively large chlorine atoms appears to dominate how these various molecules crystallize.…”
Section: Resultsmentioning
confidence: 99%
“…The smooth temperature dependence of τ α , which contrasts with the abrupt changes displayed by both σ dc and τ BNN , rules out a possible space-charge origin and points to a dipolar origin of the α relaxation (in fact, the increment of τ α has the opposite sign than σ dc at both phase changes). Structural relaxations corresponding to molecular reorientation dynamic process are observed in liquids but also in some disordered solids, such as plastic crystals or rotator phases, orientationally disordered crystals, and Condis crystals with dynamic conformational disorder . Since the α relaxation is visible in both the metastable phase and the fully ordered stable one, it cannot be ascribed to the dynamic hydrogen-bond disorder that we have observed in the metastable phase II.…”
Section: Results and Discussionmentioning
confidence: 64%
“…Structural relaxations corresponding to molecular reorientation dynamic process are observed in liquids but also in some disordered solids, such as plastic crystals 33 or rotator phases, 61 orientationally disordered crystals, 62 and Condis crystals with dynamic conformational disorder. 63 Since the α relaxation is visible in both the metastable phase and the fully ordered stable one, it cannot be ascribed to the dynamic H-bond disorder that we have observed in the metastable phase II. We can also rule out an origin related to the migration of H-bond defects (missing H-bonds) such as that reported in liquid water and ice, 46,51 as in the case of H2O it is observed that the relaxation frequency for this process increases by six orders of magnitude upon crossing the melting transition, 50 while in the EAM case there is barely any change in relaxation frequency upon melting (see inset to Figure 6(a)).…”
Section: Electric Conductivity and Dielectric Relaxations In Eammentioning
confidence: 64%